ESTETIKA TRADISONAL RAGAM HIAS ISTANA RAJA GUNUNG SAHILAN RIAU - Jenni Masrita; Ediwar Ediwar; Harrisman Harrisman (Institut Seni Indonesia Padang Panjang, 2016)
ABSTRACT This research discusses the traditional aesthetics of King Gunung Sahilan’s palace decorations in Riau. Initially, Gunung Sahilan Palace was the governmental center of Kingdom Gunung Sahilan. However nowadays, palace and its decorations become the cultural artifacts of Gunung Sahilan people. Therefore, the existence of palace and its decorations is still maintained until today. This research used the theories of sociology, aesthetics, semiotics and acculturation; and qualitative research method with its descriptive-interpretative characteristic. Palace shape and its description were described, interpreted and analyzed by observing them directly. The aesthetics of palace decorations can be seen from their shapes inspired from nature or surrounding environment. These decorations are applied on the palace roof and wall, and above the palace door and window. They contain philosophical and meaningful elements for the life of Gunung Sahilan people formed from the existed cultures. Keywords: Palace, Aesthetics, Decorations, Acculturation